Question
upstudy study bank question image url

1) a) For the following functions, find \( f \circ g \circ h \). \( f(x)=2 x-1, g(x)=x^{2}, h(x)=1-x \) b) Given the function \( F(x)=\sin ^{2}(x-3) \), find the functions \( f, g \) and \( h \) such that \( F=f \circ g \circ h \)

Ask by Bernard Pena. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1) a) \( f \circ g \circ h(x) = 2x² - 4x + 1 \) 1) b) - \( h(x) = x - 3 \) - \( g(x) = \sin x \) - \( f(x) = x² \)

Solution

1) a) We are given:   f(x) = 2x – 1,   g(x) = x²,   h(x) = 1 – x. To find (f ∘ g ∘ h)(x), start with h(x), then apply g, and finally f. Step 1: Compute h(x):   h(x) = 1 – x. Step 2: Compute g(h(x)):   g(h(x)) = (1 – x)².   Expanding: (1 – x)² = 1 – 2x + x². Step 3: Compute f(g(h(x))):   f(g(h(x))) = f((1 – x)²) = 2·(1 – x)² – 1.   Substitute the expanded form:    = 2(1 – 2x + x²) – 1    = 2 – 4x + 2x² – 1    = 2x² – 4x + 1. Thus, (f ∘ g ∘ h)(x) = 2x² – 4x + 1. ------------------------------------------------------ 1) b) We are given:   F(x) = sin²(x – 3). A convenient choice is to rewrite F(x) in a way that fits the format f(g(h(x))). Notice that:   sin²(x – 3) = [sin(x – 3)]². One possible decomposition is: • Let h(x) = x – 3. • Let g(x) = sin x. • Let f(x) = x². Then, we have:   (g ∘ h)(x) = g(h(x)) = sin(x – 3),   and   (f ∘ g ∘ h)(x) = f(sin(x – 3)) = [sin(x – 3)]² = F(x). These choices satisfy the requirement, so the functions are:   h(x) = x – 3,   g(x) = sin x,   f(x) = x².

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find \( f \circ g \circ h \), we first need to evaluate each function step by step. 1. Start with \( h(x) = 1 - x \). 2. Plug \( h(x) \) into \( g(x) \): \[ g(h(x)) = g(1 - x) = (1-x)^2 = 1 - 2x + x^2. \] 3. Now plug \( g(h(x)) \) into \( f(x) \): \[ f(g(h(x))) = f(1 - 2x + x^2) = 2(1 - 2x + x^2) - 1 = 2 - 4x + 2x^2 - 1 = 2x^2 - 4x + 1. \] Thus, \( f \circ g \circ h = 2x^2 - 4x + 1 \). For part b, to express \( F(x) = \sin^2(x - 3)\) as a composition of functions \( f, g, \) and \( h \): 1. We can let \( h(x) = x - 3 \). 2. Then, define \( g(x) = \sin(x) \). 3. Finally, let \( f(x) = x^2 \). Putting it together, we have \( F(x) = f(g(h(x))) = f(g(x - 3)) = f(\sin(x - 3)) = \sin^2(x - 3) \).

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy